Relationship between Socioeconomic Status and Family Support with Quality of Life of People Living With HIV and AIDS - Indah Maya Safitri (Universitas Airlangga, 2020)
Background: Since the beginning of HIV epidemic in the world, about 70 million people have been infected with the HIV, and 35 million have died for HIV. HIV-AIDS is a chronic disease that requires a comprehensive treatment on People Living With HIV and AIDS (PLWHA) who need family support in facing their problems. Family in a community have a different social class, one of which is socioeconomic status. Objective: This study analyzed the relationship between socioeconomic status (education level, job status, and income) and family support with the quality of life of PLWHA. Method: This study was an observational study with a cross-sectional analytic design. The population were PLWHA who were outpatients in the clinical stage 3 based on the medical records of IPIPI RSUD Dr. Soetomo Surabaya. The sample size was 93 respondents selected by using simple random sampling technique. Data were collected through self-administered instrument with WHOQOL HIV BREF and analyzed with chi-square test. The study was conducted from April to May 2018 at IPIPI RSUD Dr. Soetomo Surabaya. Results: Results showed that there was no correlation between education level (P value = 0.141), job status (P value = 1.000), and income (P value = 0.678) with the quality of life of PLWHA, and there was significant correlation of family support (P value = 0.030) with the quality of life of PLWHA. Support that is significantly related to the quality of life is social network support (P value = 0.034). Conclusion: There is no correlation of education, employment status, and income with the quality of life of People Living with HIV/AIDS (PLWHA). There is a significant correlation of social network support from families with the quality of life of PLHA.